How to identify specialization? The case of India's cities - Kala Seetharam Sridhar (Asian Development Bank Institute (ADBI), 2017)
Given that India's urban areas contribute to nearly two-thirds of its gross domestic product, even though they account for only 31% of the country's population, they have been rightly called the engines of India's growth. In this paper, I answer the following questions: What are the economic specializations of Indian cities and towns, and how have these specializations changed over time? What part of these specializations identified is due to the local advantages, and what part is due to growth of the industry or national economic growth? Answers to these questions are basic to sustaining the competitiveness of India's cities. This paper uses standard Census of India data at the level of the city, to compute location quotients for all of India's cities and towns, using the state as the reference area, and examines changes in the Indian cities' economic base over time, using an ex ante classification of states/cities. Further this paper performs shift share analyses for selected large cities of the country, to determine the country's urban specialization. I find that on average, over 1991-2001, Indian cities' specialization in manufacturing, declined. We find that no single city holds the same competitive position in a sector during the period, which implies that there is constant competition between cities even within a state. Further, in all non-agricultural economic sectors, cities in the lagging Indian states have core competence in most sectors. Based on the shift share analyses, we bust the myths that Delhi has local competence in public administration, and Mumbai is the financial capital of the country. The paper concludes with policy implications, caveats and further steps for the research.
Keywords: O18; O25; P48; R11; R12; 330; Location quotients; India's cities; Shift share; India; Regional economic tools-India; Urban competitiveness-India; Economic base; India's cities